2003
DOI: 10.1016/s0147-9563(03)00042-6
|View full text |Cite
|
Sign up to set email alerts
|

Meaning and life purpose: the perspectives of post-transplant women

Abstract: PURPOSE:A descriptive, exploratory study was conducted to examine perceptions and meanings assigned to the experience of end-stage heart failure and transplant surgery in female recipients. METHODS:Data was collected from 33 female heart transplant recipients from a heart transplant clinic using quantitative and qualitative methods. Women completed the Life Attitudes Profile and Multiple Affect Adjective Checklist and participated in a semi-structured interview. RESULTS:Women on average had a meaning score of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 14 publications
2
42
0
Order By: Relevance
“…Supporting previous research on the predictive ability of psychosocial factors on patients' QOL post-transplantation, we also found that optimism predicted better QOL [20,21].…”
Section: Discussionsupporting
confidence: 89%
“…Supporting previous research on the predictive ability of psychosocial factors on patients' QOL post-transplantation, we also found that optimism predicted better QOL [20,21].…”
Section: Discussionsupporting
confidence: 89%
“…6,7 In a previous report, we attributed the increased psychologic distress experienced by women after OHT to ongoing feelings of uncertainty, unpredictability and lack of control. 23 Intuitively, these feelings contribute to emotional distress. Similarly, women with breast cancer reported feelings of fatigue closely linked to depression; in this instance, fatigue was strongly associated with bodily pain and sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, abnormal scores among female transplant recipients were observed in a similar study beyond 5 years posttransplant surgery. 32 Transplant recipients attributed their psychologic distress to knowledge of their continuing vulnerability to major health problems including graft rejection, infection, neoplasm, and death. 33 It follows that, although cardiac transplantation relieves the dysfunction associated with HF, transplant surgery does not free patients from the influence that somatic concern exerts on dysfunction.…”
Section: Two-year Follow-up Of Qol In Patients Referred For Heart Tramentioning
confidence: 99%